The amazing story of Adolphus Tips - Morpurgo, Michael (New York : Scholastic Press, 2006)
When Boowie reads the diary that his grandmother sends him, he learns of her childhood in World War II England when American and British soldiers practiced for D-Day's invasion in the area of her home, and about her beloved cat, Adolphus Tip, and the cat's namesake.
Keywords: World War, 1939-1945 -- England -- Juvenile fiction; World War, 1939-1945 -- Fiction; Cats -- Fiction; Grandmothers -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Great Britain -- History -- George VI, 1936-1952 -- Fiction